AN EVALUATION OF DRUG COST CONTROL POLICY AT NAKHON PATHOM HOSPITAL - Kositchaiyong, Verachai; Rutanarugsa, Dararat; Loatrakul, Onanong; Thongruang, Pathomrat; Chuasoong, Chittarin (Thai Bulletin of Pharmaceutical Sciences, 2023)
Drug spending expenditure of Nakhon Pathom Hospital has been found to continuously increase through the past few years. The drug cost control policy has been implemented since the fiscal year of 2021 by the Pharmacy and Therapeutic Committee, which is divided into two main aspects namely, the price control policy and the policy of the rational use of drugs. This descriptive study aimed to assess the effectiveness and the impact of drug cost control policies on drug expenditure, which focused on the non-essential drugs, and antimicrobial drugs that are on the drug list of Nakhon Pathom Hospital. The research article is a descriptive analysis comparing drug expenditure before and after the policy implementation for 1 year. The collective data was accumulated in the fiscal year of 2020 and the fiscal year of 2021 comparatively, before and after the implementation of the drug cost control policy, respectively. The results of the study after full official implementation of the drug cost control policies showed that the drug expenditure in the fiscal year of 2021 appeared to be reduced to 39,023,292.93 baht, which was lower than the expected approval budget (8.29% reduction). Compared to the budget in the fiscal year of 2020, the reduction of the drug expenditure in the fiscal year of 2021 is 5,258,046.93 baht (1.20% reduction). The expenditure for non-essential drugs appeared to have been reduced to 13,472,900.87 baht (10.73% reduction). The use of antimicrobial drugs (DDD/100bed-day) in the group of the beta-lactam plus beta-lactamase inhibitors (BL/BI), and tigecycline was decreased, except carbapenems and colistin which had an increased cost of usage during the time of the study. This study showed that the appropriate use of restricted antimicrobial drugs was 100%. By comparison, drug expenditure on 16 groups of non-essential drugs in the fiscal year of 2021 decreased significantly from the previous year. The conclusion of the study of the drug cost control policies was to help the reduction of hospital expenditure and lead to enhance the effectiveness of financial management budgeting of Nakhon Pathom Hospital.